Peran Kesiapan Emosional Dewasa terhadap Kesejahteraan Psikologis Menjelang Usia Lanjut (Jurnal Motivasi Pendidikan dan Bahasa, 2026)
Adulthood is a crucial time for preparing for old age. During this period, a person experiences physical, mental, and social changes that can impact psychological well-being in later life. Prior to writing this article, an outreach program was conducted with adults regarding the aging process and the importance of emotional preparation to better understand and prepare them for old age. Emotional preparation encompasses a person's ability to understand, control, and express feelings wisely. Inadequate emotional preparation can increase the risk of stress, anxiety, and loneliness in old age. This study aims to examine the role of emotional preparation in adulthood on psychological well-being in old age. The method used was a literature review. The results indicate that adults with e better ablegood emotional preparation ar to adapt to life's changes in old age. Therefore, strengthening emotional preparation in adulthood is crucial to supporting psychological well-being and a healthy aging process.